Therapie der unspezifischen destruierenden Spondylodiszitis unter besonderer Berücksichtigung des sagittalen Profils = Therapy of unspecific destructive spondylodiscitis with special consideration to sagittal alignment - Klöckner, Constantin; Wiedenhöfer, Bernd (Der Orthopäde, 2012)
Nonspecific destructive spondylodiscitis is a severe illness which is accompanied by a high mortality rate. There is agreement in the literature on the indications for surgical treatment of destructive spondylodiscitis and sagittal alignment has to be considered for the operative procedure. Therefore, the operative procedure has to make considerations for the deformity, the extent of destruction, the clinical characteristics of the patient and the extent of spondylodiscitis.